Pengaruh Kinerja Keuangan dan Ukuran Perusahaan terhadap Pengungkapan CSR pada Perusahaan Bumn yang Listed di BEI Periode 2012-2017 - Novi Yanti; Nova Begawati (Journal of Economics and Management Scienties, 2023)
This study aims to determine the effect of financial performance and company size on CSR disclosure either partially or simultaneously. This research was conducted at state-owned companies listed on the Indonesia Stock Exchange in the period 2012-2017. The population in this study are all BUMN companies listed on the Indonesia Stock Exchange (IDX) for the period of 2012-2017 as many as 20 companies. The number of companies sampled in this study were 14 companies during the study period, from 2012-2017 using the purposive sampling metho The analytical method used is multiple linear regression analysis and the coefficient of determination. Hypothesis testing uses the t test and the F test. The results showed that: 1. Financial performance had a positive and significant effect on the disclosure of CSR of BUMN in the 2012-2016 period. 2. The size of the company has a positive and significant effect on the disclosure of CSR of BUMN in the 2012-2016 period. 3. The contribution of financial performance and company size to CSR disclosures is 43.9% while the remaining 56.1% is influenced by other variables such as managerial ownership, institutional ownership, leverage and others.